Diskursus Homo Digitalis dalam Tinjauan Dimensi Material dan Substansial Kebudayaan - Zandro, Agrindo (Perspektif, 2023)
The focus of this study is to explain the concept of homo digitalis in light of the material and substantial dimensions of culture. Changes are always experienced by intelligent creatures, namely humans. With this change, hu[1]mans have now become humans who are no longer called homo sapiens but homo digitalis. The birth of homo digitalis coincided with digital technology which accompanied and colored his daily life. With this technology, a homo digitalis knits and interprets the surrounding reality as his own culture. Homo digitalis is present in the world existentially and has its own culture. For this reason, this study wants to describe homo digitalis in terms of the material and substantial dimensions of culture so that everything related to homo digitalis culture can be discovered from it. The method used in this study is a qualitative method through literature study. This study found that homo digitalis has a unique and complex culture. The contribution of this study is a treasure of knowledge about homo digitalis culture which is actually a universal human reality today.